Analisis Praktik Transfer Pricing Dalam Strategi Pengelolaan Pajak Perusahaan Multinasional : Systematic Literature Review - Faza, Fazara Aspasari; Diandra, Diandra Azzahra Isabella; Lusi, Lusi Lestari; Naura, Naura Athira; Rintan, Rintan Gitaria; Sri, Sri Maryati (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2026)
In the economic sector, large-scale tax management will inevitably be subject to strict oversight by global tax authorities. Each company’s tax operations should be managed efficiently and strategically, given that tax obligations are closely tied to corporate affiliations. For multinational companies, various tax management strategies are employed, one of which is transfer pricing. However, transfer pricing faces regulatory challenges across global tax systems. Therefore, this study will comprehensively examine everything from strategic motivations, operational mechanisms, to the effectiveness of international regulations regarding transfer pricing practices. To achieve this objective, a Systematic Literature Review (SLR) following the PRISMA protocol will be conducted by analyzing two different databases: Scopus (Q1–Q3 rankings) and Google Scholar (SINTA 3–6 accreditation). Through this analysis, 17 selected articles were identified from the years 2019 to 2025, demonstrating that the sources used are highly credible and relevant. The findings of this study confirm that transfer pricing, which was initially driven by motivation, has evolved with the support of various agency factors such as tunneling incentives, as well as managerial drivers that help achieve tax efficiency. Additionally, the thin capitalization scheme, which initially utilized manipulation techniques involving physical goods transactions, was identified. Complementing these findings, strategic substitution led to tighter global regulations, compelling multinational corporations to plan for more robust domestic tax management. This study offers new perspectives and preparedness strategies within the tax sector, particularly regarding the implementation of transfer pricing.